ON FLEXURAL PHONONS IN GRAPHENE. THERMAL CONDUCTIVITY AND SPECIFIC HEAT - GROSU, I.; CRISAN, M. (Studia Universitatis Babeș-Bolyai Physica, 2019)
We analyzed the phonon spectrum of graphene. The flexural phonon contribution on thermal properties of graphene is discussed. The thermal conductivity has been calculated using the Boltzmann equation in the relaxation time approximation. The temperature dependence of the thermal conductivity and of the phonon specific heat has been calculated in the low temperatures domain.